2022
DOI: 10.1017/s0021859622000569
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the quality attributes, phenolic content and antioxidant activity of cultivated and wild asparagus as influenced by seasonal variations

Abstract: The wild asparagus Asparagus acutifolius L. is common in the Mediterranean Basin. Wild asparagus spears are an important food source within their native range, and can be used as a sustainable nutrition source. In addition, interest has risen in wild relative species of Asparagus as a source of genetic improvement in Asparagus officinalis L. In this study, the quality traits (spear colour, total soluble solid content, dry matter content and chlorophyll and sugar fractions) and health-related compounds (total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The phenolic and flavonoid contents in asparagus have been investigated in the literature. Asparagus contains different polyphenols, including hydroxycinnamic and ferulic acids, in moderate amounts as determined by HPLC analysis ( 51 ). In this context, Nile and Park ( 22 ) found that ARs had a higher polyphenol content of 28.17 GAE/100 g compared to other medicinal plants, such as Butea monosperma , Withania somnifera , Tephrosia purpurea , Vitex negudo , and Plumbago zeylanica , with polyphenol contents of 24.07 GAE/100 g, 24.02 GAE/100 g, 18.02 GAE/100 g, 12.45 GAE/100 g, and 10.21 GAE/100 g, respectively.…”
Section: Bioactive Compounds In Asparagusmentioning
confidence: 99%
“…The phenolic and flavonoid contents in asparagus have been investigated in the literature. Asparagus contains different polyphenols, including hydroxycinnamic and ferulic acids, in moderate amounts as determined by HPLC analysis ( 51 ). In this context, Nile and Park ( 22 ) found that ARs had a higher polyphenol content of 28.17 GAE/100 g compared to other medicinal plants, such as Butea monosperma , Withania somnifera , Tephrosia purpurea , Vitex negudo , and Plumbago zeylanica , with polyphenol contents of 24.07 GAE/100 g, 24.02 GAE/100 g, 18.02 GAE/100 g, 12.45 GAE/100 g, and 10.21 GAE/100 g, respectively.…”
Section: Bioactive Compounds In Asparagusmentioning
confidence: 99%